How lessons from an evolving comprehensive approach for water and sanitation can improve artisanal and small-scale mining environmental initiatives. (1st February 2021) - Schwartz, Michelle; Smits, Kathleen; Smith, Nicole; Phelan, Thomas
Abstract: Environmental risk mitigation strategies employed in developing communities to address mercury pollution from artisanal and small-scale gold mining (ASGM) have largely failed to meet community needs, resulting in their abandonment. In contrast, the water and wastewater treatment sector has gained more traction, introducing sustainable and community supported water treatment strategies. This paper discusses why initiatives in water and wastewater treatment in developing communities are succeeding while initiatives in ASGM environmental risk mitigation are falling short. Selected case studies illustrate that water and wastewater treatment project success is contingent on the inclusion of a fully comprehensive approach that considers the socio-economic and ecological context of communities and individuals along with behavior change interventions. These elements of successful WASH projects were then applied to past ASGM environmental projects to determine their applicability to the sector. By adopting the core traits of successful water and wastewater treatment projects in developing communities, a framework can be developed for ASGM projects that, when applied correctly, could lead to measurable impact and long-term sustainability.